Failing to win : perceptions of victory and defeat in international politics - Johnson, Dominic D. P., 1974-; Tierney, Dominic, 1977- (Harvard University Press, 2006)
How do people decide which country came out ahead in a war or a crisis? In Failing to Win, Dominic Johnson and Dominic Tierney dissect the psychological factors that predispose leaders, media, and the public to perceive outcomes as victories or defeats--often creating wide gaps between perceptions and reality.